A tumor microenvironment–induced absorption red-shifted polymer nanoparticle for simultaneously activated photoacoustic imaging and photothermal therapy - Wang, Shulong (Sci Adv, 2021)
Tumor microenvironment–responsive therapy has enormous application potential in the diagnosis and treatment of cancer. The glutathione (GSH) level has been shown to be significantly increased in tumor tissues. Thus, GSH can be used as an effective endogenous molecule for diagnosis and tumor microenvironment–activated therapy. In this study, we prepared a tumor microenvironment–induced, absorption spectrum red-shifted, iron-copper co-doped polyaniline nanoparticle (Fe-Cu@PANI). The Cu(II) in this nanoparticle can undergo a redox reaction with GSH in tumors. The redox reaction induces a red shift in the absorption spectrum of the Fe-Cu@PANI nanoparticles from the visible to the near-infrared region accompanying with the etching of this nanoparticle, which simultaneously activates tumor photoacoustic imaging and photothermal therapy, thereby improving the accuracy of in vivo tumor imaging and the efficiency of photothermal therapy. The nanoparticle prepared in this study has broad application prospects in the diagnosis and treatment of cancer.